The Effect Of Area Area, Production, And Number Of Workers On The Productivity Of Oil Palm Plantations In Indonesia In 2014-2023 - Hernandita Wikantyasning; Ec. Marseto (Oikonomia : Journal of Management Economics and Accounting, 2025)
This study aims to analyze the effect of area, total production, and total labor on the productivity of oil palm plantations in the 10 main oil palm producing provinces in Indonesia during the period 2014-2023. The research method used is a quantitative approach with a panel data regression model. The best model selection used Chow, Hausman, and Lagrange Multiplier tests, which resulted in the Fixed Effect Model (FEM) as the most suitable model. The results of the analysis show that area has a negative and significant effect on productivity, production has a positive and significant effect, while labor has no significant effect. The coefficient of determination (R²) of 80.21% indicates that the independent variables in this study are able to substantially explain variations in productivity. This finding indicates that there is a need to optimize land and labor management to improve the efficiency of the oil palm plantation sector in Indonesia